Letter from Edward N. Kent to James Curtis Booth, August 26, 1856 - Kent, Edward (1856)
Edward N. Kent of the United States Assay Office at New York requests a supply of large acid pitchers.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City